20-Hydroxyeicosatetraenoic Acid Inhibition by HET0016 Offers Neuroprotection, Decreases Edema, and Increases Cortical Cerebral Blood Flow in a Pediatric Asphyxial Cardiac Arrest Model in Rats. Issue 11 (November 2015) - Shaik, Jafar Sadik B; Poloyac, Samuel M; Kochanek, Patrick M; Alexander, Henry; Tudorascu, Dana L; Clark, Robert SB; Manole, Mioara D
Vasoconstrictive and vasodilatory eicosanoids generated after cardiac arrest (CA) may contribute to cerebral vasomotor disturbances and neurodegeneration. We evaluated the balance of vasodilator/vasoconstrictor eicosanoids produced by cytochrome P 450 (CYP) metabolism, and determined their role on cortical perfusion, functional outcome, and neurodegeneration after pediatric asphyxial CA. Cardiac arrest of 9 and 12 minutes was induced in 16- to 18-day-old rats. At 5 and 120 minutes after CA, we quantified the concentration of CYP eicosanoids in the cortex and subcortical areas. In separate rats, we inhibited 20-hydroxyeicosatetraenoic acid (20-HETE) synthesis after CA and assessed cortical cerebral blood flow (CBF), neurologic deficit score, neurodegeneration, and edema. After 9 minutes of CA, vasodilator eicosanoids markedly increased versus sham. Conversely, after 12 minutes of CA, vasoconstrictor eicosanoid 20-HETE increased versus sham, without compensatory increases in vasodilator eicosanoids. Inhibition of 20-HETE synthesis after 12 minutes of CA decreased cortical 20-HETE levels, increased CBF, reduced neurologic deficits at 3 hours, and reduced neurodegeneration and edema at 48 hours versus vehicle-treated rats. In conclusion, cerebral vasoconstrictor eicosanoids increased after a pediatric CA of 12 minutes. Inhibition of 20-HETE synthesis improved cortical perfusion and short-term neurologic outcome. These results suggest that alterations in CYP eicosanoids have a role in cerebral hypoperfusion and neurodegeneration after CA and may represent important therapeutic targets.